KONSTRUKSI NILAI MELALUI PENDIDIKAN OLAHRAGA - Ali Maksum (LPMPP Universitas Negeri Yogyakarta, 2009)
Sports are believed to be an effective instrument to inculcate positive values for human development. Sports provide learners with space to learn tolerance, cooperation, perseverance, discipline, competitiveness, leadership, etc. However, in reality this is not always the case, which makes experts in sports education have a lot of concern. It is necessary to find a solution if there is something wrong in sports education. It seems necessary to deconstruct and reconstruct sports education at school. This article offers a sports learning model called Sport-ed. There are two theoretical frameworks as the underlying principles, namely the constructivist approach and the experiential learning. From these perspectives, sports learning is expected to organize learners experience in the meaningful interpretation of social life. Values such as honesty, tolerance, and moral should be integrated into the basic structure of learners logic. Keywords: sports, sports education, value construction